Fasting blood glucose as a predictor of mortality: Lost in translation - Palliyaguru, Dushani L; Shiroma, Eric J; Nam, John K; Duregon, Eleonora; Vieira Ligo Teixeira, Camila; Price, Nathan L; Bernier, Michel; Camandola, Simonetta; Vaughan, Kelli L; Colman, Ricki J; Deighan, Andrew; Korstanje, Ron; et al. (Cell metabolism, 2021)
Aging leads to profound changes in glucose homeostasis, weight, and adiposity, which are considered good predictors of health and survival in humans. Direct evidence that these age-associated metabolic alterations are recapitulated in animal models is lacking, impeding progress to develop and test interventions that delay the onset of metabolic dysfunction and promote healthy aging and longevity. We compared longitudinal trajectories, rates of change, and mortality risks of fasting blood glucose, body weight, and fat mass in mice, nonhuman primates, and humans throughout their lifespans and found similar trajectories of body weight and fat in the three species. In contrast, fasting blood glucose decreased late in life in mice but increased over the lifespan of nonhuman primates and humans. Higher glucose was associated with lower mortality in mice but higher mortality in nonhuman primates and humans, providing a cautionary tale for translating age-associated metabolic changes from mice to humans.